Effects of a Structured Resource-based Web Issue-Quest Approach on Students' Learning Performances in Computer Programming Courses - Hsu, Ting-Chia; Hwang, Gwo-Jen (Educational Technology ＆ Society, 2017)
Programming concepts are important and challenging to novices who are beginning to study computer programming skills. In addition to the textbook content, students usually learn the concepts of programming from the web; however, it could be difficult for novice learners to effectively derive helpful information from such non-structured open resources. Few studies have addressed this issue by proposing different web issue-quest approaches and investigating the effects of learning with different web resources on students' learning performances in computer programming courses, not to mention the use of statistical methods for analyzing the factors affecting students' learning outcomes. Therefore, in this study, a structured-resource issue-quest approach is proposed to support structured programming learning activities. An issue-quest learning environment was developed, and an experiment was conducted to compare the learning achievement of the students who learned with the proposed approach (experimental group) with that of the students who learned with the conventional open-resource-based issue quest approach (control group). The participants were 418 tenth graders (214 in the experimental group and 204 in the control group) who were 16 years old on average. Structural Equation Modeling (SEM) was employed to investigate and compare the effects of the Web Issue-Quest approaches (i.e., open resource-based issue quest and structured resource-based issue quest) on the students' learning perceptions based on an extended technology acceptance model (ETAM). The experimental results showed that the structured resource-based issue quest approach benefited the novices more in terms of their learning achievements related to the computer programming concepts. Meanwhile, the SEM analysis showed that the two groups of students had equivalent perceptions of the usefulness, ease-of-use and enjoyment of learning with the two issue quest modes. This implies that the structured resource-based issue quest approach was helpful to the students in terms of improving their learning performance, while the limitation of access to open resources did not affect their learning perceptions.